The Tilted Self: Visuo-Graviceptive Mismatch in the Full-Body Illusion - Thür, Carla; Roel Lesur, Marte; Bockisch, Christopher J.; Lopez, Christophe; Lenggenhager, Bigna (Frontiers in Neurology, 2019)
The bodily self is a fundamental part of human self-consciousness and relies on online multimodal information and prior beliefs about one’s own body. While the contribution of the vestibular system in this process remains under-investigated, it has been theorized to be important. The present experiment investigates the influence of conflicting gravity-related visual and bodily information on the sense of a body and, vice versa, the influence of altered embodiment on verticality and own body orientation perception. In a full-body illusion setup, participants saw in a head-mounted display a projection of their own body two meters in front of them and felt tactile stimulation on their back either synchronously or asynchronously to the seen touch. By tilting the seen body to one side, an additional visuo-vestibular conflict about the body orientation with respect to gravity was created. Self-identification with the seen body was measured explicitly with a questionnaire and implicitly with skin temperature. As measures of orientation with respect to gravity we assessed the subjective haptic vertical and the haptic body orientation. Finally, we measured the individual visual field dependence using the rod-and-frame test. The results show a decrease in self-identification during the additional visuo-vestibular conflict, but no modulation of the perceived verticality or the subjective body orientation. Furthermore, explorative analyses suggest a stimulation-dependent modulation of the perceived body orientation in individuals with a strong visual field dependence only. The results suggest a mutual interaction of vestibular and other sensory signals and the individual’s weighting style in defining our sense of a bodily self.